Pengaruh Waktu Kontak dan Massa Adsorben Biji Asam Jawa (Tamarindus indica) dengan Aktivator H3PO4 terhadap Kapasitas Adsorpsi Zat Warna Methylene Blue - Rizki, Andri; Syahputra, Ervan; Pandia, Setiaty; Halimatuddahliana (Talenta Publisher (Universitas Sumatera Utara), 2019)
This study aims to determine the best adsorption capacity of methylene blue with variations in the mass of the adsorbent, contact time and determine the reaction kinetics and adsorption isotherms of activated carbon. The raw material for activated carbon is tamarind seeds. Tamarind seeds is started to neutral pH and dried in an oven at 130Â°C to a constant weight, then mashed using a blender and sifted using a 140 mesh sieve. adsorbent 140 mesh was added to 100 ml of methylene blue solution at a stirring speed 150 rpm for each variation of contact time 30 minutes, 60 minutes, 120 minutes and 180 minutes and mass of adsorbent 0,3 gs, 0,4 gs, 0,6 gs and 0,9 gs. The efficiency of the best description of methylene blue is 98,827% with 120 minutes and pH 6 at 0,9 gs of activated carbon. The maximum methylene orange adsorption capacity is 24,670 mg/g at 100 mg/L methylene blue concentration. The model suitable for this study is the second order kinetics and Freundlich adsorption isotherm. The results of the Fourier Transform Infra-Red (FTIR) spectrophotometer on the raw material of Tamarind seeds before activated were obtained by wave number which shows the presence of functional goups C-O, O-H, and C=O goups which form a special goup found on biosorbent, functional goups that appear after activation is a C=C goup which shows an increase in carbon and C-H goups (Alkenes). The results of the Scanning Electron Microscope (SEM) characterization show that the surface morphology of the activated carbon from tamarind seeds has a surface that is open, coarse, and uniform porosity. The pores of biosorbent after activation in vacant soil without impurity.